Development of digital handout of quantum mechanics no spin and quantum mechanics with spin using professional pdf flip app - Nurvita, D; Akhsan, H; Muslim, M; Ariska, M (Journal of physics. Conference series, 2022)
This study aims to produce a digital handout on the subject of mechanics quantum mechanics without spins and quantum mechanics with spins are valid and practical. Development This digital handout uses a combination of Rowntree’s development model and evaluation model Tessmer formative. The Rowntree development model consists of three stages, namely: planning, development and evaluation. The evaluation stage consists of four stages, namely: self evaluation, expert review, one-to-one evaluation, small group evaluation. Technique data collection in this study using walkthroughs and questionnaires. Research subject This is a student who has taken the introductory quantum physics class of class 2017 Indralaya class for the Physics Education Study Program, Sriwijaya University. Obtained the average scorethe average that meets the very valid category with a score on the content aspect of 4.92, the design aspect 4.46, and the language aspect 4.5. And meet the very practical category with an average score of 4.43at the one-to-one evaluation stage and 4.52 at the small group evaluation stage.